F(1)+F(-2)=7-9x

Simple and best practice solution for F(1)+F(-2)=7-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(1)+F(-2)=7-9x equation:


Simplifying
F(1) + F(-2) = 7 + -9x

Reorder the terms for easier multiplication:
1F + F(-2) = 7 + -9x

Reorder the terms for easier multiplication:
1F + -2F = 7 + -9x

Combine like terms: 1F + -2F = -1F
-1F = 7 + -9x

Solving
-1F = 7 + -9x

Solving for variable 'F'.

Move all terms containing F to the left, all other terms to the right.

Divide each side by '-1'.
F = -7 + 9x

Simplifying
F = -7 + 9x

See similar equations:

| 5+5x=41-x | | (2x-3)=4z-1 | | 2u+12=-3 | | x^2-0.1111= | | 96x-8=20 | | 7+y(b+1)=c | | 2u+13=-3 | | 13x+3=-19+3x | | 3x+17=8x-18 | | x^2-.25= | | (-2+3i)+(5-2i)= | | 2+3*8=a | | -7+3x-8x=2-8x | | 4(x-3)+2=3x-10+x | | 5by-a=b(b+2y) | | (x+4)+3=17 | | x^2-0.25= | | 2*2*2*2*2=a | | x=8-2y | | 2y-3b=5y-9 | | 3x^2+9x+x+3+4x^2+8x+8x+16-19=0 | | 12x+19=6x+5 | | 2e+38=2(5e-4)-2 | | 6y^3-24y=0 | | 4x+23=13x-39 | | 7-3n+n=n-1+8 | | 11=1+6k+4k | | 3*3*3*3=a | | 24-2s=20(25-3) | | (13)49+7(-6)+(-36)= | | y^4-14y^2+40=0 | | R-2=6 |

Equations solver categories